THE GRAMMATICAL ERRORS IN STUDENTS’ WRITING DESCRIPTIVE TEXT AT ENGLISH EDUCATION PROGRAM ISLAMIC UNIVERSITY OF BATANGHARI - Ridwan, Adang; Karmila, Ria (La Ogi : English Language Journal, 2024)
The aim of this study was to grammatical errors in students’ writing descriptive text at second semester English Language Education at Universitas Islam Batanghari. This is a qualitative research, the research employing documentation to collect data and data analysis in this research was descriptive analysis. The result of the study showed that the common types of grammatical errors made by the students at second semester English Language Education at Islamic University of Batanghari were omission error occurs because student omits some important items that must appear in the sentence, addition error occurs because student gets failure to omit unimportant item in sentence, misformation error occurs because students use be and verb together in simple present sentence and misordering error occurs because students make the sentence has incorrect placement item and addition of preposition. And the dominant errors made by the students at second semester English Language Education at Islamic University of Batanghari is Omission error because from five 5 data itself consist of two topics of descriptive text students always make mistake in Omission error. It was possibly caused by carelessness of the students. The carelessness was often closely related to lack of motivation